Disease control programs in developing countries: Prospects and constraints - Perry, Brian D. (Sydney University, 1997)
In this paper, prospects and constraints are considered for improved disease control programs under four features of disease control, viz, problem identification and characterization, availability of effective disease control technologies (vaccines, drugs, etc.), methods to deliver the technologies and the knowledge as to their effective use, and successful adoption and use of control measures by farmers. The examples and experience summarized in this chapter refer to various types of disease and regions.